(untitled) (Nexo Revista Científica, 2022)
In the conditions of the continuing crisis, determined both by external sanctions against Russia from several Western states, and the ongoing coronavirus pandemic, it is the industrial ecosystems of the country’s regions that form innovative solvations with subjects of other industries and spheres of activity and are the main rational consumers of regional resources that combine the potential of innovative speed, high quality, adaptation to changing consumer demands, etc. This article examines the scientific and practical problem of the formation and functioning of innovation-oriented industrial solvates, the solution of which is in line with the new approach proposed by the authors to identify, determine the sources and rank the effects of innovative solvations in the regional industry. This approach is built on the concept of a circular economy, which is based on the assumption of the most rational organization and use of all types of resources of integrated industrial enterprises and related industries (spheres of activity), including through the use of end-to-end digital technologies. It has been proved that in various phases of the economic cycle, effective resource provision of solvation processes in the system of industrial innovations is of decisive importance, which means not only the rational distribution of limited resources between the participants of innovative solvations but also their lean and waste-free use in the production process.